University English Learners Designing Digital Multimodal Texts about the Academic Community - Velandia Santamaría, Jessica Marcela; Quintero, Luz Mary (Colombian Applied Linguistics Journal, 2025)
Today's education must address the challenges posed by an increasingly linguistically diverse society, in which communication has been profoundly reshaped by advances in information and communication technologies. In response to this complex communicative landscape, a qualitative action research study was conducted with a group of undergraduate students enrolled in an intermediate English course at a public university in Colombia. The study aimed to examine to what extent students maximize meaning making in English through the creation of multimodal texts within their university community. During the didactic intervention, which incorporated community pedagogy, multimodal activities were interwoven to scaffold students' multimodal text design. Data were collected through a teacher’s journal, interviews and students’ multimodal eBooks. The findings revealed that multimodality was a powerful means to make community members visible, highlight social issues, and inspire social transformation. Finally, the combination of community pedagogies and multimodality effectively promoted meaning-making in the target language, enhancing students' linguistic competence and critical literacy practices.